총의치의 납의치 상에서 치은 형성 시행 후에 나타나는 시간에 따른 인공 치아 이동에 대한 평가 - 이세한(Sea-Han Lee); 곽영훈(Young-Hun Kwak); 김희중(Hee Jung Kim) (구강회복응용과학지, 2018)
목적: 치은 형성 후 인공치아의 이동에 대하여 평가를 시행하였다. 연구 재료 및 방법: 10벌의 동일한 치아배열과 치은의 외형을 가진 납의치를 이용하여 실험하였다. 이 납의치 상에서 치은형성을 시행하였고, 10분 간격으로 120분 간 모델 스캔을 시행하여 치아 간 거리를 측정하였다. SPSS Ver. 22. 0를 이용하여통계학적 분석을 시행하였다. 결과: 치은 형성 후 평균적으로 치아 사이의 거리가 0.0999 mm에서 0.1787 mm로 나타났다. 인공치아 이동의 변화율에대해서는 40 - 50분과 50 - 60분 사이와 50 - 60분과 60 - 70분 사이에서 통계학적으로 유의한 차이가 관찰되었고, 그 이후에는 변화율의 유의한 차이가 없었다. 결론: 120분 간 측정한 결과 인공치아의 이동이 관찰되었고, 60 - 70분 이후에는 시간에 따른 평균 이동량의 변화가 관찰되지 않았다. 이를 종합하면, 치은 형성 후 60분 이상 경과된 시점에서 교합에 대한 재평가를 시행한 후에 최종 의치를 제작하는 것이 필요하다. Purpose: The purpose of this study was to evaluate the deformation of the complete denture artificial teeth arrangement after festooning over time. Materials and Methods: 10 wax dentures of equal teeth arrangement and equal gingival contour were used in this study. Festooning of the wax dentures were conducted and 3D model scans were conducted every 10 minutes for 120 minutes. Interdental transverse distances were measured with the scanned images. Statistical analyses were performed with SPSS Ver. 22. 0. Results: Interdental transverse distance between teeth varied from 0.0999 mm to 0.1787 mm. Mean rate of deformation showed statistically significant change between the 40 - 50 minute interval and 50 - 60 minute interval and between the 50 - 60 minute interval and 60 - 70 minute interval. No statistically significant change of the mean rate of deformation was observed later on. Conclusion: Monitoring of the interdental transverse distance for 120 minute after festooning have shown the deformation and displacment of the artificial teeth arrangement. From after the 60 - 70 minute interval after festooning, the mean deformation showed no statistically significant change of the mean rate of deformation was observed. Within the limitations of this in vitro study results suggest that the final occlusal adjustment in wax denture before complete denture curing should be proceeded at least 60 minutes later after festooning. KCI Citation Count: 1